The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1085/jgp.20028583
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Tacrine Block at Adult Human Muscle Nicotinic Acetylcholine Receptors

Abstract: We used single-channel kinetic analysis to study the inhibitory effects of tacrine on human adult nicotinic receptors (nAChRs) transiently expressed in HEK 293 cells. Single channel recording from cell-attached patches revealed concentration- and voltage-dependent decreases in mean channel open probability produced by tacrine (IC50 4.6 μM at −70 mV, 1.6 μM at −150 mV). Two main effects of tacrine were apparent in the open- and closed-time distributions. First, the mean channel open time decreased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
2
28
1
Order By: Relevance
“…acetylcholine receptors expressed in M10 cells is 38 AM (Svensson and Nordberg, 1997) and for adult human muscle type nicotinic acetylcholine receptors expressed in HEK293 is 309 AM (Prince et al, 2002). With these values as reference, the present estimate of 14 AM for the apparent functional affinity of tacrine for human a4h2 nicotinic acetylcholine receptors does not appear unrealistic.…”
Section: Potentiating Effects Of Cholinergic Drugsmentioning
confidence: 58%
See 2 more Smart Citations
“…acetylcholine receptors expressed in M10 cells is 38 AM (Svensson and Nordberg, 1997) and for adult human muscle type nicotinic acetylcholine receptors expressed in HEK293 is 309 AM (Prince et al, 2002). With these values as reference, the present estimate of 14 AM for the apparent functional affinity of tacrine for human a4h2 nicotinic acetylcholine receptors does not appear unrealistic.…”
Section: Potentiating Effects Of Cholinergic Drugsmentioning
confidence: 58%
“…A more sophisticated mechanism is required to account for the anomalous concentration dependence of inhibition by galanthamine and rivastigmine. Various models for block of adult human muscle nicotinic acetylcholine receptors expressed in HEK293 cells by tacrine have been evaluated using single-channel data (Prince et al, 2002). The detailed kinetic analysis suggested that tacrine blocks the channel by binding to two sites in the open channel and to a site in the closed channel of the receptor.…”
Section: Inhibitory Effects Of Cholinergic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…If this distant effect involves a 1:1 interaction with first-order rate constants, the nonluminal inhibitor will add a single exponentially decaying population of closings whose mean duration does not vary with inhibitor concentration. Any other combination of effects on open and closed channel durations would suggest a more complicated mechanism of inhibitor action, as commonly reported (46).…”
Section: Right Column Of Traces) This Solution Has a Nominal CLmentioning
confidence: 66%
“…Many data suggest that the major subtypes of channels in rat hippocampal interneurons are composed of the ␣7 and ␣4␤2 subunits (Alkondon and Albuquerque, 1993;Jones and Yakel, 1997;Frazier et al, 1998;McQuiston and Madison, 1999). Tacrine, which was one of the first drugs used to treat AD (Terry and Buccafusco, 2003), was not a potentiator of nAChRs (Zwart et al, 2000;Samochocki et al, 2003) but rather inhibited the function of various nAChRs (Canti et al, 1998;Zwart et al, 2000;Prince et al, 2002). Huperzine A is isolated from the Chinese herb Huperzia serrata and enhances cognitive function (Zangara, 2003).…”
mentioning
confidence: 99%